2012
DOI: 10.1186/2191-219x-2-2
|View full text |Cite
|
Sign up to set email alerts
|

99mTc-MAG3 scintigraphy for the longitudinal follow-up of kidney function in a mouse model of renal ischemia-reperfusion injury

Abstract: BackgroundExperimental models are essential tools in the development and evaluation of novel treatment options, but the preclinical model of renal ischemia-reperfusion injury is limited to the retrieval of (very) early functional data, leaving the pivotal long-term outcome unknown. The present study applies technetium-99m-mercapto-acetyl-tri-glycine [99mTc-MAG3] scintigraphy for the longitudinal follow-up examination of long-term kidney function after renal ischemia-reperfusion injury.MethodsUnilateral warm is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Results of the scans at week one, six and eleven are not shown. As described previously, preserved renal function is observed by a fast and steep increase of [ 99m Tc]Tc-MAG3 in the kidneys with rapid excretion as well as preserved FUR values comparable to baseline [16,17]. The renal curve in group 1 (placebo) is almost unchanged compared to baseline.…”
Section: Bun Creatinine and Blood Count During Follow-upsupporting
confidence: 61%
See 2 more Smart Citations
“…Results of the scans at week one, six and eleven are not shown. As described previously, preserved renal function is observed by a fast and steep increase of [ 99m Tc]Tc-MAG3 in the kidneys with rapid excretion as well as preserved FUR values comparable to baseline [16,17]. The renal curve in group 1 (placebo) is almost unchanged compared to baseline.…”
Section: Bun Creatinine and Blood Count During Follow-upsupporting
confidence: 61%
“…[ 99m Tc]Tc-MAG3-scintigraphy was performed as described in previously published protocols [14][15][16][17]. Inhalational anaesthesia with 2.0% of isoflurane in pure oxygen was induced and maintained with a concentration of 1.5%.…”
Section: Renal Scintigraphymentioning
confidence: 99%
See 1 more Smart Citation
“…MR-Imaging studies investigating acute kidney injury observed indirect changes such as alteration of the cortical and medullary T2-relaxation-time or reduced perfusion [36] [39] . A MR-technique quantifying tissue anisotropy as an indirect measure of tubular integrity is Tensor Imaging, commonly based on diffusion (DTI) [7] , [40] [42] or as described recently on susceptibility (STI) [43] .…”
Section: Discussionmentioning
confidence: 99%
“…Glomerular filtration rate (GFR) is considered the best indicator of overall kidney function for early monitoring and optimization of therapeutic interventions (1,2). However, the accurate quantification of GFR, which is of particular importance in the setting of clinical research, still remains challenging (3,4).…”
mentioning
confidence: 99%